The U3 small nucleolar ribonucleoprotein component Imp4p is a telomeric DNA-binding protein - Hsieh, Yi-Ching (Portland Press Ltd., 2007)
Imp4p is a component of U3 snoRNP (small nucleolar ribonucleoprotein) involved in the maturation of 18S rRNA. We have shown that Imp4p interacts with Cdc13p, a single-stranded telomere-binding protein involved in telomere maintenance. To understand the role of Imp4p in telomeres, we purified recombinant Imp4p protein and tested its binding activity towards telomeric DNA using electrophoretic mobility-shift assays. Our results showed that Imp4p bound specifically to single-stranded telomeric DNA in vitro. The interaction of Imp4p to telomeres in vivo was also demonstrated by chromatin immunoprecipitation experiments. Significantly, the binding of Imp4p to telomeres was not limited to yeast proteins, since the hImp4 (human Imp4) also bound to vertebrate single-stranded telomeric DNA. Thus we conclude that Imp4p is a novel telomeric DNA-binding protein that, in addition to its role in rRNA processing, might participate in telomere function.